Endothelial Progenitor Cells Attenuate Ventilator-Induced Lung Injury with Large-Volume Ventilation. Issue 12 (December 2019) - Ju, Ying-nan; Geng, Ying-jie; Wang, Xue-ting; Gong, Jing; Zhu, Jingli; Gao, Wei
Ventilator-induced lung injury (VILI) is a common complication that results from treatment with mechanical ventilation (MV) in acute respiratory distress syndrome (ARDS) patients. The present study investigated the effect of endothelial progenitor cell (EPC) transplantation on VILI. Wistar rats were divided into three groups ( n = 8): sham (S), VILI model (V) induced by tidal volume ventilation (17 mL/kg), and VILI plus EPC transplantation (VE) groups. The lung PaO2 /FiO2 ratio, pulmonary wet-to-dry (W/D) weight ratio, number of neutrophils, total protein, neutrophil elastase level, and inflammatory cytokines in bronchoalveolar lavage fluid (BALF) and serum were examined. Furthermore, the histological and apoptotic analysis, and lung tissue protein expression analysis of Bax, Bcl-2, cleaved caspase-3, matrix metalloproteinase (MMP)-9, total nuclear factor kappa B (total-NF-κB), phosphorylated NF-κB (phospho-NF-κB) and myosin light chain (MLC) were performed. The ventilation-induced decrease in PaO2 /FiO2 ratio, and the increase in W/D ratio and total protein concentration were prevented by the EPC transplantation. The EPC transplantation (VE group) significantly attenuated the VILI-induced increased expression of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-8, MMP-9, phospho-NF-κB and MLC, neutrophil elastase levels and neutrophil counts in BALF. In addition, the anti-inflammatory factor IL-10 increased in the VE group. Furthermore, pulmonary histological injury and apoptosis (TUNEL-positive cells, increase in Bax and cleaved caspase-3) were considerably diminished by the EPC transplantation. The EPC transplantation ameliorated the VILI. The mechanism may be primarily through the improvement of epithelial permeability, inhibition of local and systemic inflammation, and reduction in apoptosis.